The system of fertigation-advising by the open-field vegetable growing with environment-protecting view - Terbe, István; Slezák, Katalin; Kappel, Noémi (Acta Agraria Debreceniensis, 2012)
The changed economical surroundings and the more strict ecological rules induced a need of changes also of the system of advisory on nutrient-supply of vegetable growing. There were many experiences and scientific results born after the last summarizing vegetable fertilization directives (1981), which allowed finishing a new system of advisory mentioned and presented above. We are sure, that the new directives, based on the modern view of vegetable production and also laying on economical possibilities will help the domestic vegetable production to stay competitive on the domestic and the foreign markets both.